2014
DOI: 10.1016/b978-0-444-54314-1.00008-2
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rates and Interest Parity

Abstract: This essay is to appear as a chapter in the Handbook of International Economics, vol. 4 (Elsevier), edited by Gita Gopinath, Elhanan Helpman, and Kenneth Rogoff. I thank Philippe Bacchetta and Fabio Ghironi, as well as Gita Gopinath and Ken Rogoff for helpful comments. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(142 citation statements)
references
References 198 publications
6
128
1
Order By: Relevance
“…More recently, Scholl and Uhlig (2008) recon…rm the result and …nd that the exchange rate peaks between 17 and 26 months after a monetary shock. These …ndings are in contrast to UIP predictions, and as such have proven di¢ cult to 1 explain (see Engel, 2013). Our approach to account for transaction services of treasuries leads to an endogenous liquidity premium that can contribute to explaining the observed exchange rate reactions to changes in interest rates di¤erentials.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…More recently, Scholl and Uhlig (2008) recon…rm the result and …nd that the exchange rate peaks between 17 and 26 months after a monetary shock. These …ndings are in contrast to UIP predictions, and as such have proven di¢ cult to 1 explain (see Engel, 2013). Our approach to account for transaction services of treasuries leads to an endogenous liquidity premium that can contribute to explaining the observed exchange rate reactions to changes in interest rates di¤erentials.…”
Section: Introductioncontrasting
confidence: 48%
“…However, the empirical literature has shown that the UIP prediction fails not only conditional on monetary policy shocks, but also unconditionally. This is evidenced in the kind of empirical tests conducted by Fama (1984) and many others surveyed in Froot and Thaler (1992) and Engel (2013). The negative association between interest rate di¤erentials and depreciation rates seems to hold in general.…”
Section: Unconditional Correlationsmentioning
confidence: 75%
“…Examining data on different currencies and spanning distinct sample periods, Sarno and Sojli (2009) and Balke et al (2013, hereafter BMW) identify a 1 Engel (2014) provides the most recent survey on past studies on nominal exchange rates. 2 Nominal exchange rates, therefore, need to Granger-cause future economic fundamentals, not vice versa.…”
mentioning
confidence: 99%
“…An important step forward in this strand of research was that these models can be now brought to the data via the use of advanced estimation techniques (An and Schorfheide, 2007). From an econometric perspective, recent writings have also convincingly presented evidence that models estimated with large panels of data are able to outperform the RW in exchange rate forecasting (Engel, 2013;Ince, 2014). This suggests that the dismal forecasting performance of exchange rate models can be partly attributed to estimation rather than mis-specification error.…”
Section: Introductionmentioning
confidence: 99%